Diagnosis of Congenital Muscular Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Patterns of alkaline and acid phosphatases were compared with the distribution of merosin and dystrophin staining in muscle biopsies from 20 children with congenital muscular dystrophy (CMD) examined at the Department of Neurology, Washington University School of Medicine, St Louis, MO.